2015
DOI: 10.7314/apjcp.2015.16.4.1665
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Simultaneous Resection of Gastric Primary Tumour and Synchronous Liver Metastases: Survival Analysis of a Single-center Experience in China

Abstract: Background: The optimal surgical strategy for the treatment of synchronous resectable gastric cancer liver metastases remains controversial. The aims of this study were to analyze the outcome and overall survival of patients presenting with gastric cancer and liver metastases treated by simultaneous resection. Materials and Methods: Between January 1990 and June 2009, 35 patients diagnosed with synchronous hepatic metastases from gastric carcinoma received simultaneous resection of both primary gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The 5-year OS and RFS rates in our study are similar to those reported in previous studies. The OS and RFS rates reportedly ranged from 9.3% to 42.1% and from 8.6% to 27.7%, respectively (3)(4)(5)(6)(7)(12)(13)(14)(15)(16)(17)(18). The median OS time was 38.0 months for selected patients in our study, which was also comparable to previous studies, where it ranged from 11 to 36 months (3,6,15,16,18,19).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The 5-year OS and RFS rates in our study are similar to those reported in previous studies. The OS and RFS rates reportedly ranged from 9.3% to 42.1% and from 8.6% to 27.7%, respectively (3)(4)(5)(6)(7)(12)(13)(14)(15)(16)(17)(18). The median OS time was 38.0 months for selected patients in our study, which was also comparable to previous studies, where it ranged from 11 to 36 months (3,6,15,16,18,19).…”
Section: Discussionsupporting
confidence: 87%
“…According to previous studies that included > 30 (108) patients in the past 5 years, multiple liver metastases, R1/R2 resection, synchronous metastases, maximum size of liver metastases, pT4 of primary tumor, and other distant metastases were reported to be risk factors for OS (3,5,6,16,18,19). Unlike the previously reported covariates, the diffuse-type adenocarcinoma in our study is one of the prognostic factors for OS and RFS, and it is a predictor of extra-liver metastasis development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC is one of the most common cancers in China, with high mortality due to its aggressiveness, and poor prognosis (1113). Although a number of genes and signaling pathways involved in GC development have been identified (1417), the mechanism is still too sophisticated to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The resection of distant metastases, however, did not significantly improve the survival compared to those patients in which only the primary tumor was removed [25]. In a small study on 35 Chinese patients undergoing both resection of the primary tumor and synchronous hepatic metastatic disease, Liu et al [26] identified lymphovascular invasion of the primary tumor and multiple liver metastases as negative prognostic factors for survival.…”
Section: Discussionmentioning
confidence: 99%